The imbalanced anterior and posterior default mode network in the primary insomnia. (August 2018) - Yu, Siyi; Guo, Baojun; Shen, Zhifu; Wang, Zhengyan; Kui, Yu; Hu, Youping; Feng, Fen
Abstract: Neuroimaging studies have demonstrated that the brain is altered both structurally and functionally in patients with primary insomnia (PI). However, most previous hypothesis-driven studies of PI might bias observations. Here, we use global functional connectivity density (gFCD), a hypothesis-free approach, to investigate the brain functional alteration in patients with PI. Forty-eight patients with PI and 51 matched healthy control (HC) subjects were recruited and underwent a resting state functional magnetic resonance imaging (fMRI) scan. Analyses of group differences of gFCD in the whole brain and the clinical significances of abnormal brain function were conducted. Compared with the HC group, patients with PI showed increased gFCD in the executive control network, salience network, dorsal attention network, and visual network. Interestingly, the gFCD in the anterior default mode network (DMN) is increased in the PI group, whereas the gFCD in the posterior DMN is decreased. In addition, the increased gFCD in the insula is associated with higher Pittsburgh Sleep Quality Index scores in the PI group. The gender and duration of disease have no significant effects on abnormal gFCD network. This study is the first attempt to explore the gFCD feature in patients with PI. Our findings support the hyperarousal model of insomnia and suggest an imbalanced neural spontaneous fluctuation between anterior and posterior DMN in the resting state in patients with PI. These findings expand our understanding of the neuropathological mechanism of primary insomnia. Highlights: Global functional connectivity density (gFCD) was used to explore the brain functional alteration in primary insomnia. Patients with PI showed altered gFCD in the executive control, salience, dorsal attention, and visual network. Patients with PI showed an imbalanced neural spontaneous fluctuation between anterior and posterior DMN. The increased gFCD in insula is associated with more severe insomnia.